Spatiotemporal elements in a poisoned bait strategy against the long-tailed silverfish (Lepismatidae: Zygentoma). - Bjørn Arne Rukke; Morten Hage; Anders Aak (PLoS ONE, 2021)
The long-tailed silverfish Ctenolepisma longicaudatum (Lepismatidae: Zygentoma) is a nuisance problem in buildings and a major concern in museums, libraries and archives where it cause damage to historical and priceless items. We used laboratory bioassays and two field studies of infested buildings to evaluate spatial and temporal elements of a poisoned bait strategy. In both laboratory experiments and field studies, the efficiency of poisoned bait with indoxacarb as the active ingredient was significantly improved by placing many small bait droplets evenly distributed along all edges of the treated area compared to more clustered distributions. Extended duration of bait presence and removal of competing food sources improved the control effect significantly in the laboratory bioassays. Bait-treated populations also showed a significant decline in the number of eggs deposited and emergence of new nymphs. The study supports poisoned bait as an efficient and low risk approach against the long-tailed silverfish in which extended duration of bait presence, wide distribution of bait droplets in combination with sanitation was crucial for control in the infested premises.